2021
DOI: 10.3390/agronomy11112124
|View full text |Cite
|
Sign up to set email alerts
|

Disease Severity, Resistance Analysis, and Expression Profiling of Pathogenesis-Related Protein Genes after the Inoculation of Fusarium equiseti in Wheat

Abstract: Wheat (Triticum aestivum) is an important cereal crop, grown throughout the temperate and in some tropical and sub-tropical zones, at higher elevations. Several biotic and abiotic factors influence the production of wheat. In the present study, two wheat varieties have been subjected to disease severity and resistance analysis against Fusarium equiseti. Disease severity analysis revealed Shafaq-2006 to be more resistant than Sahar-2006. Both varieties were further subjected to the expression analysis of six im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Bt can also directly promote plant growth by synthesizing phosphate lysing enzymes [ 60 ], siderophores [ 61 ], and plant hormones [ 62 , 63 ]. When analyzing the growth-promoting effects of GBAC46 and NMTD81 strains in rice, it was found that the selected strains significantly promoted rice physiological parameters such as root and shoot length [ 10 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bt can also directly promote plant growth by synthesizing phosphate lysing enzymes [ 60 ], siderophores [ 61 ], and plant hormones [ 62 , 63 ]. When analyzing the growth-promoting effects of GBAC46 and NMTD81 strains in rice, it was found that the selected strains significantly promoted rice physiological parameters such as root and shoot length [ 10 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rates of Gene Expression Detection (%) x y Single KTP-03-non-inoculated (1) and -inoculated (lines 2-9) leaf type I trichomes (corresponding to Figure 2) and single hyphae-removed trichomes that possessed one (10) or three (11) haustoria (corresponding to Figure 3). z Not detected.…”
Section: Methodsmentioning
confidence: 99%
“…Also, Sunera et al [10] suggested that the use in agriculture of plant growth promoting bacteria (PGPB), isolated from tomato rhizospheres, stimulated plant growth and reduced environmental risks by providing a sustainable agro-ecosystem. In addition, Manghwar et al [11] studied the behavior of important PR genes in different wheat varieties, identifying which genes could be used for cloning into wheat and other transgenic crops to create resistance to Fusarium equiseti.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, achieving stronger resistance can be achieved by stacking/pyramiding different traits, and in this regard, CRISPR-Cas-induced HDR should be further encouraged ( Pandolfi et al, 2017 ). Furthermore, pattern recognition receptor (PRR) transfer has been demonstrated to confer broader and more robust resistance in Arabidopsis and tomatoes ( Lacombe et al, 2010 ; Saqib et al, 2020 ), banana and rice ( Tripathi et al, 2014 ), and wheat ( Manghwar et al, 2021 ). This is feasible owing to the maintenance of comparable immune signaling systems in monocots and dicots ( Holton et al, 2015 ).…”
Section: Transgenic Techniques That Use Crispr-cas Systems To Enhance...mentioning
confidence: 99%